2016
DOI: 10.3758/s13420-016-0236-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate and proximate mechanisms of reciprocal altruism in rats

Abstract: The reciprocal exchange of goods and services among social partners is a conundrum in evolutionary biology because of its proneness to cheating, but also the behavioral and cognitive mechanisms involved in such mutual cooperation are hotly debated. Extreme viewpoints range from the assumption that, at the proximate level, observed cases of Bdirect reciprocity^can be merely explained by basic instrumental and Pavlovian association processes, to the other extreme implying that Bcultural factors^must be involved,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
16
1
Order By: Relevance
“…This increased pulling propensity of hungry rats cannot be explained by a mislead expectation to obtain food for themselves, because rats pulling with the same hunger state showed reduced pulling rates when pulling the platform towards an empty cage. Hence, their increased pulling rate for a partner when being hungry reflects neither a self-directed immediate feeding demand nor an undirected change in motivation (Dolivo, Rutte, & Taborsky, 2016). All rats participating in the experiment had experienced this variant of the iterated Prisoner's dilemma paradigm before.…”
Section: Discussionmentioning
confidence: 99%
“…This increased pulling propensity of hungry rats cannot be explained by a mislead expectation to obtain food for themselves, because rats pulling with the same hunger state showed reduced pulling rates when pulling the platform towards an empty cage. Hence, their increased pulling rate for a partner when being hungry reflects neither a self-directed immediate feeding demand nor an undirected change in motivation (Dolivo, Rutte, & Taborsky, 2016). All rats participating in the experiment had experienced this variant of the iterated Prisoner's dilemma paradigm before.…”
Section: Discussionmentioning
confidence: 99%
“…Like rats4647, dogs seem to understand the need of a partner to make them act cooperatively (see also ref. 33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was also argued that the change in leading-following states over trials is in line with the mutually beneficial exchange between a cooperator and a reciprocating partner [39], which is a form of direct reciprocity–a basic form of reciprocal cooperation [[35]. Indeed, recent laboratory studies demonstrated that wild rats display a generalized reciprocity that does not depend on the identity of the recipient [8], a direct reciprocity in which the partners are familiar [9, 11, 14], and that they help the more hungry recipients or those in poor condition [10]. Other studies have demonstrated reciprocity in laboratory rats, suggesting that the mechanism for this reciprocity is a display of food-seeking behavior [40], and that prosocial behavior in rats occurs even in the absence of strategic, reciprocal, or selfish motivations [38].…”
Section: Discussionmentioning
confidence: 99%